2017
DOI: 10.13152/ijrvet.4.2.4
|View full text |Cite
|
Sign up to set email alerts
|

The Lack of Collaboration Between Companies and Schools in the German Dual Apprenticeship System: Historical Background and Recent Data

Abstract: On the macro level (federal level) and exo level (state or regional level), the German Dual Apprenticeship System shows a high degree of institutionalised collaboration. However, the companies and vocational schools on the meso level (institutional level and level of the actors), in contrast, are just loosely coupled with a dominant partner (i.e., companies) and a subordinate partner (i.e., vocational schools). How and why these structures have emerged, established and stabilised is part of a complex historica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
10

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 12 publications
0
46
0
10
Order By: Relevance
“…The long history of the formation and development of dual education in such European countries as Germany Austria, Switzerland determines the application of an integrated approach to the study and application of the system in new countries of implementation. The history of formation and the problem of the cooperation of stakeholders of dual education in Germany are covered in [3]. The history of the development of the German model of dual education reveals the dominance of companies in the model and the lack of cooperation between companies and schools.…”
Section: Research Of Existing Solutions Of the Problemmentioning
confidence: 99%
“…The long history of the formation and development of dual education in such European countries as Germany Austria, Switzerland determines the application of an integrated approach to the study and application of the system in new countries of implementation. The history of formation and the problem of the cooperation of stakeholders of dual education in Germany are covered in [3]. The history of the development of the German model of dual education reveals the dominance of companies in the model and the lack of cooperation between companies and schools.…”
Section: Research Of Existing Solutions Of the Problemmentioning
confidence: 99%
“…In previous research, different scholars have revealed different aspects of coherence-related challenges. Recently, Gessler (2017) and Louw (2017) pointed to the lack of cooperation between schools and workplaces in the German and Danish dual apprentice system. Louw's study showed that closer cooperation between the teachers in schools and the instructors in the workplaces enhanced the students' experience of the relationship between the learning arenas.…”
Section: The Norwegian Education Programme For Media and Communicationmentioning
confidence: 99%
“…At the same time, securing one's own demand for skilled workers is the most important reason why German companies participate in dual vocational education and training (Merrilees, W. J. 1983;Niederalt 2005;Jansen, Pfeifer, Schönfeld & Wenzelmann, 2015, Gessler 2017).…”
Section: Introductionmentioning
confidence: 99%